Expression profile of eight glutathione S-transferase genes in Crassostrea ariakensis after exposure to DSP toxins producing dinoflagellate Prorocentrum lima. (October 2015) - Zou, Ying; Wei, Xiao-Meng; Weng, Hui-Wen; Li, Hong-Ye; Liu, Jie-Sheng; Yang, Wei-Dong
Abstract: In this study, changes in eight GSTs mRNA level including GST-α, GST-σ, GST-ω, GST-π, GST-μ, GST-ρ, GST-θ and microsomal GST (mGST) in the oyster Crassostrea ariakensis after exposure to Prorocentrum lima have been evaluated by quantitative real-time PCR. Additionally, the contents of five GST isoforms were detected by ELISA. After exposure to P. lima at density of 2 × 10 5  cells/L, mGST mRNA significantly increased in gill, while GST-σ was induced in digestive gland. After exposure to P. lima at density of 2 × 10 6  cells/L, GST-ω and mGST expressions increased in gill, whereas GST-α and GST-σ were induced in digestive gland. The GST content and activity in oysters exposed to P. lima also showed a different pattern when the different isoforms and organs were compared. After exposure to P. lima (2 × 10 6  cell/L), GST-π increased in gill but decreased in digestive gland. The total GST enzyme activity increased in gill, while remained unchanged in digestive gland. These various regulation of GST gene expressions indicated that the GSTs isoenzymes might play divergent physiological roles in the detoxification of DSP toxins in C. ariakensis . Highlights: Eight GSTs mRNA levels in C. ariakensis after exposure to P. lima were evaluated. P. lima exposure caused differential expressions of GST isoforms. GST isoenzymes might play divergent roles in detoxification of DSP toxins.